2020
DOI: 10.7759/cureus.10169
|View full text |Cite
|
Sign up to set email alerts
|

A Single Centre Randomised Control Study to Assess the Impact of Pre-Operative Carbohydrate Loading on Women Undergoing Major Surgery for Epithelial Ovarian Cancer

Abstract: Historically, patients have fasted before elective surgery to ensure an empty stomach to avoid aspiration. A fasting-induced catabolic state however may adversely influence recovery after surgery. Our study was designed to test the effect of oral carbohydrate loading on clinical parameters in patients undergoing major surgery for advanced-stage ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…After adjusting factors that may affect length of hospital stay, the authors found no difference between the groups in regard to morbidities. The results of the present study are comparable to those of Al-Hirmizy et al ( 11 ). However, despite the lack of a randomized control group, the present study included a larger number of patients and more homogenous and consistent data with respect to baseline patient characteristics compared with Al-Hirmizy et al ( 11 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After adjusting factors that may affect length of hospital stay, the authors found no difference between the groups in regard to morbidities. The results of the present study are comparable to those of Al-Hirmizy et al ( 11 ). However, despite the lack of a randomized control group, the present study included a larger number of patients and more homogenous and consistent data with respect to baseline patient characteristics compared with Al-Hirmizy et al ( 11 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although there are various studies reporting ERAS outcomes in gynecological oncology ( 18 ), only one study has specifically investigated the impact of carbohydrate loading as a single element of ERAS on clinical outcomes. In a single-center RCT, Al-Hirmizy et al ( 11 ) randomized 75 patients with EOC to receive a carbohydrate-enriched drink (n=37) or placebo (n=38). The authors initially found that carbohydrate loading increased the length of hospital stay by one day compared with the placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the type of the placebo in general, plain water is one option (19,30,31,38,42,43,44), but in this case, patients could be able to identify the difference between the drug and placebo by its sweetness, hence blinding is questionable. An alternative option is the use of arti cial sweeteners (27,29,33,34,45,46,47,48, but in this case, one cannot exclude their metabolic effects (19). In our meta-analysis, the used placebos differed greatly in the studies.…”
Section: Length Of Hospital Staymentioning
confidence: 96%
“…Twenty studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), including 2116 patients, used LOS as an outcome, when investigating effects of CHO-loading. Fourteen (15-28) of these studies used fasting and seven applied placebos in the control groups (19,27,(29)(30)(31)(32)(33), and two of them used both comparisons (19,27). LOS in the CHO-group vs the Fasting-group was shorter (MD: -1,71 [95% CI: -3.04, -0,38] p<0.01) (Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 99%